Kontekstualitas Fikih Perempuan di Indonesia - Rizal Darwis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
In reality, women are still considered to be second to men, both from the private and social aspects. This article discusses the contextuality of women in the private and social spheres in Indonesia. This research was studied with a juridical, normative and sociological approach. The results show that the understanding of some people in understanding religion still places religious arguments related to misogynism in positioning men and women in the private and social spheres. Even though in some religious arguments it does not differentiate it. Likewise, in the state guarantee through statutory regulations in Indonesia, the position of citizens is equal before the state, both men and women in the private and public or social spheres.